Individual differences in attachment anxiety shape the association between adverse childhood experiences and adult somatic symptoms. (March 2020) - Lin, Hung-Chu; Yang, Yang; Elliott, Luke; Green, Eric
Abstract: Background: Although prior research has documented the link between adverse childhood experiences (ACEs) and somatic symptoms, it remains unclear why some individuals exposed to ACEs developed somatic symptoms while others did not. Objective: Framed by a biopsychosocial perspective, this study investigated the role of attachment anxiety in the association between ACEs and somatic symptoms in adulthood. Participants and Setting: A total of 662 emerging adults attending college were recruited to respond to an online survey in a computer lab. Method: The computer-based survey included demographic form, the Adverse Childhood Experience Scale, the Experience in Close Relationship Scale–Short Form, and the Somatization Scale of the Symptom Checklist–90—Revised for somatic symptoms. Multivariate regression analyses were used to examine the role of attachment anxiety in the association between ACEs and somatic symptoms. Results: The results indicated that ACEs positively correlated with attachment anxiety and somatic symptoms; and attachment anxiety and somatic symptoms were positively correlated. Moreover, the results indicated a significant effect of interaction between ACEs and attachment anxiety on somatic symptoms, suggesting a moderating role of attachment anxiety. Subsequent simple slope test revealed that attachment anxiety intensified the strength of relation between ACEs and somatic symptoms; but when the level of attachment anxiety was low, ACEs and somatic symptoms were not related. Conclusion: Individual differences in attachment anxiety shape the association of adverse childhood experiences with somatic symptoms. Targeting and reformulating anxious working models of attachment may help ameliorate vulnerability to somatic symptoms in individuals exposed to ACEs.